(Potential) patients like me: testing the effects of user-generated health content on social media. Issue 2 (3rd April 2018) - Mou, Yi; Shen, Fuyuan
Abstract : As media technology becomes increasingly participatory, individuals may use social media to share health information and connect with those who have similar health concerns. While prior research has focused on evaluating the feasibility, usability, and effectiveness of traditional health messages, this study investigates the effects of user-generated health content on individuals' cognitive and emotional responses, as well as their behavioral intentions. An experimental study with a two (story source: personal story vs news story) by two (story ending: happy ending vs sad ending) factorial design was conducted. The results confirmed the positive effects of identification with the narrative character on the experience of being transported, which further led to the behavioral intentions to take countermeasures and viral communication on social media. The sad ending of a narrative was found to elicit emotions that were sufficiently strong to increase perceptions of susceptibility to dengue fever, which, however, failed to result in behavioral intentions.